PENINGKATAN AKTIVITAS DAN HASIL BELAJAR MATA PELAJARAN BIOLOGI MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) - sugio sugio bakri (Jurnal Pembelajaran Biologi: Kajian Biologi dan Pembelajarannya, 2014)
Abstract: Efforts to improve biological activity and learning outcomes, need to do Classroom Action Research (CAR) by applying a type of learning model Numbered Heads Together (NHT) in KD. 1.1, 1.2, and 1.3. Research subjects were students class XI IPA-1 SMA 20 Palembang which consists of 36 people. The procedure adopted consisted of 3 cycles, consisting of a cycle I as much as 2 meetings, cycle meetings 3 times II, and III cycle 3 times the meeting. Based on observations of student activity levels, cycles I to III has reached the category of moderately active and very active. Post-test values are achieved by students at each end of both meetings each cycle. Before the action, the value of daily tests 1,2, and 3 only reached 54.8 exhaustiveness classical. After the measures showed an increase in a row from the cycle I: 80.47 cycles II: 83.88, and the cycle III: 85.44. Before the KKM measures the percentage of daily tests are: 49.33%. After the action the percentage of students who achieve KKM (scores â‰¥ 72) increases, cycle I: 88%, cycle II: 100%, and cycle III is also 100%. Observations indicate that the activity of students in the group, tasks, think together, and answer the post test questions. The results of class XI student learning IPA-1 SMA Negeri 20 Palembang increased and implemented in response to learning good or positive. Key words: Numbered Heads Together, the results of studying Biology